2010
DOI: 10.1007/s11104-010-0610-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term simulated nitrogen deposition increases carbon sequestration in a Pleioblastus amarus plantation

Abstract: In order to understand the influence of nitrogen (N) deposition on the key processes relevant to the carbon (C) balance in a bamboo plantation, a twoyear field experiment involving the simulated deposition of N in a Pleioblastus amarus plantation was conducted in the rainy region of SW China. Four levels of N treatments: control (no N added), low-N (50 kg N ha −1 year −1 ), medium-N (150 kg N ha −1 year −1 ), and high-N (300 kg N ha −1 year −1 ) were set in the present study. The results showed that soil respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 76 publications
(107 reference statements)
9
34
0
2
Order By: Relevance
“…That is, the old-growth subtropical forests and forests dominated by N-fixing species (tree age > 30 years) (Zhang et al, 2012) were grouped into N-rich ecosystems as they have high soil N concentrations and plant growth in these ecosystems is not limited by N availability (Lu et al, 2010). Early successional forests (Mo et al, 2007;Tu et al, 2010), temperate forests and grasslands, were grouped into N-limited ecosystem because they have low soil N level and plant growth in these ecosystems is limited by N availability. N addition levels were classified into three classes, including low N (LN; 60 kg N ha À1 yr À1 ), medium N (MN; 61e120 kg N ha À1 yr À1 ), and high N (HN; > 120 kg N ha À1 yr À1 ).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the old-growth subtropical forests and forests dominated by N-fixing species (tree age > 30 years) (Zhang et al, 2012) were grouped into N-rich ecosystems as they have high soil N concentrations and plant growth in these ecosystems is not limited by N availability (Lu et al, 2010). Early successional forests (Mo et al, 2007;Tu et al, 2010), temperate forests and grasslands, were grouped into N-limited ecosystem because they have low soil N level and plant growth in these ecosystems is limited by N availability. N addition levels were classified into three classes, including low N (LN; 60 kg N ha À1 yr À1 ), medium N (MN; 61e120 kg N ha À1 yr À1 ), and high N (HN; > 120 kg N ha À1 yr À1 ).…”
Section: Data Collectionmentioning
confidence: 99%
“…Hence the degree of N deposition and its potential effects on the C cycle in Chinese terrestrial ecosystems should be different and are of increasing global concern due to the increasing interest in regional aspects of the global C cycle (Piao et al, 2009). Several N deposition monitoring programs and increased N deposition simulation experiments have been conducted since the late 1990s (Mo et al, 2006;Niu et al, 2010;Tu et al, 2010;Xu et al, 2009). Liu et al (2011) recently presented a description of the effects of N deposition on ecosystem C cycling in China.…”
Section: Introductionmentioning
confidence: 99%
“…For increasing the accuracy, all data in both fenced and grazed grassland (from three subplots) were parameterized into one regression equation. Then, in each sampling day, we only got one Q 10 value for both fenced and grazed grassland, and the standard error (SE) of apparent Q 10 values were computed by the method of Tu et al (2011). We averaged SR and MR from the 12 collars in each subplot, and the means were used to represent each subplot for analysis.…”
Section: Data Analyses and Statisticsmentioning
confidence: 99%
“…Wang et al (2014) [38] showed that the root biomass of C. angustifoliawas significantly enhanced by N deposition and the increased apportioning of biomass to root was of major significance. Plant respiration rates would increase with increasing tissue N and root biomass under N addition [39]. Therefore, elevated N deposition may result in higher C loss by increasing both autotrophic and heterotrophic respiration.…”
Section: Effect Of N Deposition On Soil Co 2 Emissionmentioning
confidence: 99%